Trends in oil and gas corrosion research and technologies production and transmission - El-Sherik, A. M. (Duxford, England Woodhead Publishing, 2017)
Trends in Oil and Gas Corrosion Research and Technologies: Production and Transmission delivers the most up-to-date and highly multidisciplinary reference available to identify emerging developments, fundamental mechanisms and the technologies necessary in one unified source. Starting with a brief explanation on corrosion management that also addresses today’s most challenging issues for oil and gas production and transmission operations, the book dives into the latest advances in microbiology-influenced corrosion and other corrosion threats, such as stress corrosion cracking and hydrogen damage just to name a few. In addition, it covers testing and monitoring techniques, such as molecular microbiology and online monitoring for surface and subsurface facilities, mitigation tools, including coatings, nano-packaged biocides, modeling and prediction, cathodic protection and new steels and non-metallics. Rounding out with an extensive glossary and list of abbreviations, the book equips upstream and midstream corrosion professionals in the oil and gas industry with the most advanced collection of topics and solutions to responsibly help solve today’s oil and gas corrosion challenges.--Provided by publisher.
Electronic reproduction.
Keywords: Corrosion and anti-corrosives.; Petroleum industry and trade -- Equipment and supplies -- Corrosion; Gas industry -- Equipment and supplies; Electronic books